Analisis Strategi Pembelajaran IPA untuk Meningkatkan Kemampuan Berpikir Kritis Siswa: Literature Review (2014-2023) - Amrullah, Lalu Azikri; Muliadi, Irman; Isnaini, Ahmad Hardyan; Nurmayanti, Nurmayanti; Anugraheni, Audy Sintia (Indonesian Journal of Teacher Education, 2024)
Critical thinking skills are essential competencies in 21st-century science education, yet Indonesian students' achievements in scientific literacy and reasoning remain relatively low. This study aims to map and analyze trends in effective science learning strategies to enhance students' critical thinking skills through a systematic literature review. The method employed is a Systematic Literature Review (SLR) of 10 national and international scientific articles published between 2014 and 2023 across Google Scholar, SINTA, and ERIC databases. The review results indicate that student-centered learning strategies consistently have a positive impact on critical reasoning. The findings are classified into four main groups: (1) discovery and inquiry strategies; (2) problem-based and project-based learning (PBL & PjBL); (3) information and communication technology (ICT) integration; and (4) contextual and cooperative approaches. The synergy between active learning models and interactive digital media support is proven to be the key factor in transforming students' evaluation and analysis skills.